2015
DOI: 10.1007/s13197-015-1828-x
|View full text |Cite
|
Sign up to set email alerts
|

Relative bioavailability of folate from the traditional food plant Moringa oleifera L. as evaluated in a rat model

Abstract: Moringa oleifera is an affordable and rich source of dietary folate. Quantification of folate by HPLC showed that 5-formyl-5,6,7,8-tetrahydrofolic acid (502.1 μg/100 g DW) and 5,6,7,8-tetrahydrofolic acid (223.9 μg/100 g DW) as the most dominant forms of folate in M. oleifera leaves. The bioavailability of folate and the effects of folate depletion and repletion on biochemical and molecular markers of folate status were investigated in Wistar rats. Folate deficiency was induced by keeping the animals on a fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(22 citation statements)
references
References 45 publications
0
20
0
1
Order By: Relevance
“…A recent study showed that iron from M. Oleifera can overcome iron deficiency and modulate the expression of iron-responsive genes better than conventional iron supplements (Saini et al, 2014a). Similarly, Saini et al (2016) found that the relative bioavailability of folate from M. Oleifera leaves using rat model was very high (approx. 82%) suggesting that the M. Oleifera leaves can be a potential source of dietary folate.…”
Section: Nutritional Value Of M Oleiferamentioning
confidence: 99%
“…A recent study showed that iron from M. Oleifera can overcome iron deficiency and modulate the expression of iron-responsive genes better than conventional iron supplements (Saini et al, 2014a). Similarly, Saini et al (2016) found that the relative bioavailability of folate from M. Oleifera leaves using rat model was very high (approx. 82%) suggesting that the M. Oleifera leaves can be a potential source of dietary folate.…”
Section: Nutritional Value Of M Oleiferamentioning
confidence: 99%
“…Moringais known to be a significant source of foliate with higher bioavailability compared to other vegetables. 35 High-performance liquid chromatography i.e. HPLC-DAD-MS/ MS based method developed by Santos et al 36 allows a simple and sequential extraction and monitoring of several free forms of water soluble vitamins (vitamins C, B1, B2, B3, B5, B6 and B9) and fatsoluble vitamins (pro-vitamin A and vitamin E) present in raw green leafy vegetables Table 1.…”
Section: Introductionmentioning
confidence: 99%
“…The varying concentrations of phenolics with the antioxidant capacity of the tested foliage established 'Pakistan Black' and 'Techiman' as the most nutritive cultivars, compared to the other major cultivars of M. oleifera from Pakistan [41]. [42]. Additionally, these forms are highly bio available in animals, compared to other folaterich foods, such as green leafy vegetables.…”
Section: Phytochemical Constituentsmentioning
confidence: 98%